2007
DOI: 10.1016/j.str.2007.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interactions between a Recombinant IgE Antibody and the β-Lactoglobulin Allergen

Abstract: Allergies are caused by the immune reaction to commonly harmless proteins, allergens. This reaction is typified by immunoglobulin E (IgE) antibodies. We report the crystal structure of an IgE Fab fragment in complex with beta-lactoglobulin (BLG), one of the major allergens of bovine milk. The solved structure shows how two IgE/Fab molecules bind the dimeric BLG. The epitope of BLG consists of six different short fragments of the polypeptide chain, which are located especially in the beta strands, covering a fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
149
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(161 citation statements)
references
References 50 publications
12
149
0
Order By: Relevance
“…The size of the allergen-antibody interface (ϳ870 Å 2 ) is similar to the interfaces in a variety of other antibody-antigen complexes (32). In particular, the size of the interface is comparable to those found in three other allergen-antibody complexes (10,11,33).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The size of the allergen-antibody interface (ϳ870 Å 2 ) is similar to the interfaces in a variety of other antibody-antigen complexes (32). In particular, the size of the interface is comparable to those found in three other allergen-antibody complexes (10,11,33).…”
Section: Discussionsupporting
confidence: 64%
“…In fact, because of dimerization, one epitope in each allergen would be enough to cross-link IgE antibodies. Recently, the crystal structure of a complex of ␤-lactoglobulin and Fab from IgE antibodies of a combinatorial scFv phage display library showed that the allergen is a dimer, and that the Fab fragments are located in positions such that the dimeric ␤-lactoglobulin would be able to cross-link two IgE antibodies (11). Our results suggest that allergen dimerization plays a role in allergenicity to Bla g 2, by increasing IgE antibody cross-linking, in agreement with a study with engineered dimers of carrot allergen Dau c 1 (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the recognition of the ␣-Gal epitope by nature clearly contradicts the hypothesis deduced from crystal structures with proteins that IgE epitopes are preferably defined by large surface areas comprising several structural elements (45,46). This epitope and probably all types of CCD epitopes represent classical IgG epitopes.…”
Section: Discussionmentioning
confidence: 91%
“…Although at first realized using murine antibodies (42)(43)(44), co-crystals revealing the nature of authentic IgE epitopes remain scarce due to the lack of human monoclonal IgE antibodies. As a result, only two structures of allergen-IgE complexes are available so far (45,46). A peculiarity of anti-CCD antibodies is that effectual epitope is constituted by the carbohydrate itself and that it is closely related in humans and other animals.…”
Section: Discussionmentioning
confidence: 99%